2018
DOI: 10.1002/qua.25643
|View full text |Cite
|
Sign up to set email alerts
|

DFT study into the reaction mechanism of CO methanation over pure MoS2

Abstract: Mo-based catalysts are commonly used in the direct methanation of CO; however, no integrated mechanism has been proposed due to limits in characterizing the nano-sized active structures of MoS 2 . Thus, we report our investigation into the mechanism of CO methanation over pure MoS 2 through density functional theory simulations, considering that only MoS 2 edge sites exhibit catalytic activity. Simulations revealed the presence of (010) and (110) surfaces on the MoS 2 edges.Both surfaces are reconstructed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Moreover, only one C–Mo bond or C–O bond can be maintained. In addition, according to our previous work, the possibility of the existence of CH 3 O species was very small, and therefore, CH 2 OH was formed immediately. Followed by the formation of CH 2 OH, the C–O bond was further weakened, which contributed to the rupture of the C–O bond to form C*H 2 and O*H, finally leading to hydrogenation of C*H 2 to the target product CH 4 .…”
Section: Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, only one C–Mo bond or C–O bond can be maintained. In addition, according to our previous work, the possibility of the existence of CH 3 O species was very small, and therefore, CH 2 OH was formed immediately. Followed by the formation of CH 2 OH, the C–O bond was further weakened, which contributed to the rupture of the C–O bond to form C*H 2 and O*H, finally leading to hydrogenation of C*H 2 to the target product CH 4 .…”
Section: Results and Discussionmentioning
confidence: 76%
“…Schematic diagram showing reactants, intermediates, and products in three different pathways (a) and comparison of the energy profiles of optimal reaction paths for edge site and S-vacancy site on MoS 2 catalysts (b) . Reproduced with permission from ref . Copyright 2010 John Wiley and Sons.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Hence, the bridging S 2 2– played a positive effect on the hydrodesulfurization reaction. It has been verified that the proton reduction activities of various MoS x samples are intimately related to the type of S atoms by theoretical simulations. The apical S atoms located in the a-MoS x samples were fully coordinated, which was considered noncatalytic . Consequently, the binding energy corresponding to 163.19 and 164.37 eV is mainly assigned to the bridge S 2 2– .…”
Section: Resultsmentioning
confidence: 89%
“…These electron-rich metallic edge states enhance the transfer of electrons from MoS 2 to the reaction intermediates. Similarly, Li et al reported that MoS 2 ’s stable edges could catalyze CO reduction to methane. Among the exposed edges of MoS 2 , the zigzag (zz) edges (S- and Mo-terminated) are more stable .…”
Section: Introductionmentioning
confidence: 95%
“…Some previous studies focused on MoS 2 examined only the pathway for CO 2 electroreduction to CO and did not investigate the mechanism of the formation of CH 4 , , with the assumption that the potential-determining step (PDS) is *CO → *CHO. Other studies considered the formation of CH 4 but did not examine the multiple competing pathways leading to it. ,, Note that a comprehensive analysis of all of the underlying mechanisms of any chemical process is of paramount importance as the latter may involve multiple competing pathways that may be extremely sensitive to the catalyst type and active site. To address this knowledge gap in the literature, in this study, we use quantum-mechanical DFT calculations to computationally explore the mechanism for the electrochemical Sabatier reaction on pristine and doped MoS 2 edges using an implicit solvation scheme with water as the solvent.…”
Section: Introductionmentioning
confidence: 99%